Review of monetary policy in South Africa since 1994. - Aron, J; Muellbauer, J (CSAE (University of Oxford), 2006)
This paper reviews the design and performance of monetary policy in South Africa (SA) during 1994-2004. Quantitative indexes of transparency reveal a strong rise in the transparency and accountability of monetary policy between 1994 and 2004. Inflation and interest rate expectations data and forward interest rate data are used to demonstrate the increased credibility and reasonable predictability of monetary policy since adopting inflation targeting in 2000. The SA Reserve Bank's view on monetary policy transmission channels is discussed, and its recent forecasting performance is evaluated. We find that monetary policy decisions taken in response to external and domestic shocks under inflation targeting have significantly improved relative to the preceding framework, though data quality has been a constraint. Further, inflation targeting has not disadvantaged potential investment in terms of the level of tax-adjusted real interest rates. Finally, the important role for complementary policies to support monetary policy is motivated.